2010
DOI: 10.1016/j.trsl.2009.10.004
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear factor-kappa B (NFκB) component p50 in blood mononuclear cells regulates endothelial tissue factor expression in sickle transgenic mice: implications for the coagulopathy of sickle cell disease

Abstract: Sickle cell anemia is accompanied by activation of coagulation and thrombosis. We have studied the abnormal expression of tissue factor (TF) by the pulmonary vein endothelium of the mild-phenotype NY1DD sickle transgenic. As detected by immunofluorescence microscopy, this appears only after the NY1DD mouse is exposed to hypoxia/reoxygenation (H/R), which actually causes ischemia/ reperfusion in the sickle-but not the normal-mouse. We tested the hypothesis that the NFκB-activating inflammation that develops in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
45
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 40 publications
(50 citation statements)
references
References 32 publications
4
45
0
Order By: Relevance
“…Thus, the relevant effect of H/R on triggering TF expression is exerted early after cessation of hypoxia, in the first few hours of the reoxygenation period, consistent with our previous observations of many other parameters post-H/R [4,5,6], even though maximal expression of actual TF protein requires many hours longer [3]. These results suggest not only that NO may be of therapeutic benefit but also that endogenous NO could be a regulator of TF expression, as influenced by inflammation.…”
Section: Modulation By Inhaled Nosupporting
confidence: 90%
See 3 more Smart Citations
“…Thus, the relevant effect of H/R on triggering TF expression is exerted early after cessation of hypoxia, in the first few hours of the reoxygenation period, consistent with our previous observations of many other parameters post-H/R [4,5,6], even though maximal expression of actual TF protein requires many hours longer [3]. These results suggest not only that NO may be of therapeutic benefit but also that endogenous NO could be a regulator of TF expression, as influenced by inflammation.…”
Section: Modulation By Inhaled Nosupporting
confidence: 90%
“…Elsewhere, we have unambiguously demonstrated that this TF expression mouse is triggered by the inflammatory state that is known to develop in the NY1DD mouse on exposure to H/R [6]. We believe that the documented presence of an inflammatory state in the hBERK1 mouse [8] also possibly accounts for its TF expression even at ambient air, although this has not been unambiguously proven.…”
Section: Discussionmentioning
confidence: 80%
See 2 more Smart Citations
“…Previous work has also shown the role of NF-kB signaling in blood mononuclear cells in regulating endothelial tissue factor expression in sickle transgenic mice with implications for the coagulopathy of SCD. 41 The current data further emphasize the association of pathways such as inflammation, T-cell signaling, and coagulation in the development of SCD complications from HgS polymerization. Patients in cluster 1 demonstrated a greater propensity toward a more severe clinical profile as evidenced by a higher WBC count, a trend toward more severe hemolytic anemia, and history of ACS, all of which are markers of poor outcomes in SCD.…”
Section: Training Cohort Testing Cohort West African Children Cohortmentioning
confidence: 57%